Scientific Opinion on Flavouring Group Evaluation 65, Revision 1 (FGE.65Rev1): Consideration of sulfur‐substituted furan derivatives used as flavouring agents evaluated by JECFA (59th meeting) structurally related to a subgroup of substances within the group of 'Furfuryl and furan derivatives with and without additional side‐chain substituents and heteroatoms from chemical group 14' evaluated by EFSA in FGE.13Rev2 (2011). (18th February 2015) - ,; ,
Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (the JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The substances are evaluated through a stepwise approach that integrates information on structure‐activity relationships, intake from current uses, toxicological threshold of concern, and available data on metabolism and toxicity. FGE.65 concerns a group of 33 sulfur‐substituted furan derivatives evaluated by the JECFA at their 59th meeting. The Panel concluded in FGE.65 that the evaluation could not be finalised for four of the 33 substances [FL‐no: 13.056, 13.160, 13.193 and 13.194] due to lack of toxicity data. In the present revision of FGE.65, the toxicity data requested in FGE.65 for [FL‐no: 13.160] have now become available. These toxicity data are also considered to cover the evaluation of [FL‐no: 13.193 and 13.194], but not [FL‐no: 13.056]. Based on the new data the Panel agrees with the JECFA conclusion, 'No safety concern at estimated levels of intake as flavouring substances' based on the MSDI approach for 32 of the furan derivatives. For one substance [FL‐no: 13.056] a request for additional toxicity data still remains. Besides the safety assessment of these flavouring substances, the specifications for the materials of commerce have also been considered and for all 33 substances, the information is adequate.